PERAN BUDGET EMPHASIS DALAM MEMODERASI HUBUNGAN PARTISIPASI ANGGARAN TERHADAP SENJANGAN DAN KINERJA MANAJERIAL (Studi Pada 30 SKPD Kota Ternate) - Kahar, Suleman H. A.; Hormati, Asrudin (Department of Accounting, Faculty of Economics & Business,Diponegoro University, Indonesia, 2017)
This study aims to empirically test the effect of budgetary participation on budgetary slack and managerial performance. The study aims to empirically examines whether budget emphasis moderates budget participation on budget slack and managerial performance of Municipality Government of Ternate. Using moderated regression analysis, this study found that, 1) budgetary participation negatively affect budgetary slack 2) budget participation influences managerial performance and 3) budget emphasis moderates the relationship between budget participation on budgetary slack and managerial performance. The theoretical implications of this study indicate that agency and contingency theory could be used as a complement to a more effective budget participation process by integrating the expected performance measurement framework.